A Culture of Fire: Identifying Community Risk Perceptions Surrounding Prescribed Burning in the Flint Hills, Kansas - Zoey Rosen; Giovanna Henery; Kellin D Slater; Olivia Sablan; Bonne Ford; Jeffrey R Pierce; Emily V Fischer; S. L. Magzamen (Journal of Applied Communications, 2023)
In the Flint Hills region of eastern Kansas, there is a long tradition of spring prescribed burns. However, air quality concerns in downwind communities have sparked conversation regarding the environmental and social impacts of these burns. This study aimed to identify the risk perceptions associated with prescribed burns using two theoretical frameworks: the social amplification of risk framework and the protective action decision model. In April 2022, we conducted 18 in-depth, semi-structured interviews with Flint Hills community members from different social stations. Participants identified several benefits of prescribed burns: cattle production gains, invasive species management, prairie ecological health maintenance, and wildfire prevention. Some participants viewed prescribed burning as a protective response. However, risk perceptions differed between rural and urban participants: rural community members were primarily concerned with prescribed fires that went out of control, while those in downwind cities were primarily concerned with smoke exposure. Participants sometimes used protective actions to mitigate their risks, but also explained the complexities of changing burn practices that are integral to the local culture, economies, and greater society. Additionally, formal communication of health and safety risks from prescribed burns is not uniform across Kansas counties. We therefore recommend systematic county and statewide communication of burn practices and protective behaviors. Understanding community perceptions of the risks and effects of prescribed burns, and any protective actions taken, can inform how professional communicators approach burning in similar agricultural and ranching communities.
Keywords: prescribed burning; risk communication; air quality; health